Antenna Thousandfold Miniaturization with Ohmic-Biased Transistor Circuit - Shuyu Wang; Yongjian Zhang; Zhenyu Liu; Jinlong Zhang; Ziheng Zhou; Wenhua Chen; Zhijun Zhang; Xi Chen; Kunpeng Wei; Yue Li (Electromagnetic Science)
Antennas are essential components of any wireless system due to their irreplaceable functions in transmitting and receiving electromagnetic waves. Antenna radiation is based on the free electron resonance, leading to a concrete relation between its physical size and operating frequency. This fundamental principle makes it unrealizable to design well-radiated antennas with extremely small dimensions, e.g., milli-wavelength scales. Here, to overturn this commonsense correlation, an extremely miniaturization methodology of antennas is developed by integrating an arbitrary-sized antenna with an ohmic-biased transistor (OBT) circuit. In this way, we thousandfold miniaturize the antenna to an overall size at milli-wavelength scales, including the OBT circuits. Proven by the experiments in the demonstration systems, the wireless system with this thousandfold miniaturized antenna receives electromagnetic waves well. This methodology would be widely utilized in space-limited wireless systems that cannot provide enough space for antennas, benefiting various exciting areas, such as information technologies, photoelectricity physics, biomedical science, and so on.